Enantioselective Reductive Diarylation of Alkenes by Ni-Catalyzed Domino Heck Cyclization/Cross Coupling - Wang, Kuai; Kong, Wangqing (Synlett, 2019)
A Ni-catalyzed enantioselective reductive diarylation of alkenes through a tandem Heck cyclization/cross coupling of two structurally distinguished aryl bromides is accomplished for the first time. This reaction takes place under very mild conditions with high efficiency and tolerates a variety of functional groups. Thus, it provides a rapid access to various medicinally relevant bis-heterocycles containing all-carbon quaternary centers with very high enantioselectivity.
Keywords: enantioselective reactions; diarylation; alkenes; nickel catalysis; reductive cross coupling